Anti-Alopecia Activity and Compound Content of n-Hexane Fraction of Cyclea Barbata Leaves - Resmi Mustarichie (Journal of Global Pharma Technology, 2020)
One of the plants empirically used by the Pasemah tribe in South Sumatra, Indonesia,  as a hair grower is the green cincau (Indonesian) leaf (Cyclea barbata Miers.). Objective: The aim of this study was to determine the anti-alopecia activity and its compound content from the n-hexane fraction of the C. barbata leaves. Methods: Green grass jelly (C. barbata Miers.) Extracted with 96% ethanol and fractionated with water, n-hexane and ethyl acetate. The concentration of ethanol extract was diluted to 5%, 10%, 15%, 20% and 25% and all fractions were tested on rabbits by the modified Tanaka method. All data were analyzed statistically by ANOVA. Results: Test results showed that the ethanol extract of green grass jelly leaves had the activity of stimulating hair growth starting at a concentration of 15%. It was found that the n-hexane fraction had the best activity compared to other fractions and positive control (minoxidil 2%).Further tests using IR and LC-MS spectrophotometers found that the n-hexane fraction contained 1,4-dimethyl-1,2,3,6-tetrahydro-8H-pyrrolo[2’,3’:3,4]azepino[2,1-b]quinazolin-8-one. Conclusions: Ethanol extract and hexane fraction at concentrations of 15% and above were found to have anti-alopecia activity. The compound contained from the hexane fraction 1,4-dimethyl-1,2,3,6-tetrahydro-8H-pyrrolo[2’,3’:3,4]azepino[2,1-b]quinazolin-8-one] (C22H18N3O) which was thought to cause properties hair growth.Keywords: Hair loss, Anti-alopecia, Green grass jelly, Cyclea barbata Miers,  1,4-dimethyl-1,2,3,6-tetrahydro-8H-pyrrolo[2’,3’:3,4]azepino[2,1-b]quinazolin-8-one.